PENGARUH HEDONIC MOTIVATION, ELECTRONIC WORD OF MOUTH, PERCEIVED EASE OF USE, DAN PERCEIVED USEFULLNESS TERHADAP PURCHASE INTENTION LIVE STREAMING TIKTOK SHOP - Rohmatulloh, Farhan; Astuti, Novika Candra (STIE AMA Salatiga, 2024)
Abstract : This research endeavors to ascertain the impact of electronic word of mouth, hedonic motivation, perceived ease of use, and perceived usefulness on the purchase intentions of consumers participating in TikTok Live Streaming. Employing a quantitative research methodology, the study utilized a survey technique, wherein questionnaires were disseminated to a sample of 100 students from Widyatama University who have engaged in transactions through the TikTok Shop. The data collected were subjected to multiple linear regression analysis to determine the relationships among the variables. The findings of the study reveal that electronic word of mouth, hedonic motivation, perceived ease of use, and perceived usefulness significantly and positively affect purchase intentions.Abstrak : Penelitian ini bertujuan untuk mengkaji pengaruh electronic word of mouth, hedonic motivation, perceived ease of use, dan perceived usefulness terhadap purchase intention pada konsumen yang berpartisipasi dalam Live Streaming TikTok. Metode yang diterapkan dalam penelitian ini adalah metode kuantitatif dengan pendekatan survei, di mana kuesioner disebarkan kepada 100 mahasiswa Universitas Widyatama yang telah melakukan transaksi di TikTok Shop. Data yang dikumpulkan dianalisis menggunakan uji regresi linier berganda. Hasil analisis menunjukkan bahwa electronic word of mouth, hedonic motivation, perceived ease of use, dan perceived usefulness memiliki pengaruh positif yang signifikan terhadap purchase intention.